Baltų kalbų žodžių tvarkos raida tipologijos požiūriu - Ambrazas, Vytautas (Baltistica, 2005)
THE DEVELOPMENT OF WORD ORDER IN BALTIC FROM A TYPOLOGICAL VIEWPOINTThe inherited word order type DH, in which dependent is placed before head, has been preserved up till now in most Lithuanian and Latvian word order patterns, e.g.: GenN, AdjN, DemN, AdvV, AdvAdj, AdvAdv1. Historical analysis reveals the former prevalence of DH order both in the distribution of main sentence components (SOV) and in the comparative clauses (StComp). On the other hand, a tendency to place head before dependent manifests itself in the expansion of the SVO sentence pattern and of comparative clauses with a postposed standard (CompSt) during the recent history of Lithuanian and Latvian.The early stage of HD order development in Baltic is represented by prepositional constructions. They are based on ancient clauses with preverbs, which modified the meaning of nouns and verbs and had the status of dependent components. Preverbs preceding verbs maintained their dependent status; they turned into verbal prefixes later. But preverbs preceding nouns changed their relation and became heads of prepositional constructions, i.e. prepositions governing cases.Reanalysis of preposed preverbs as prepositions caused a deviation from the prevailing word order type and paved the way to the use of HD patterns in other constructions. Contacts with Slavic languages stimulated this change. A relative chronology of expansion of some HD patterns in Baltic can be presented in the following sequence: Prep - CompSt - (S)VO.
Keywords: baltų kalbos; žodžių tvarka; SVO